2017
DOI: 10.3389/fendo.2017.00181
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and Oxytocin Reduce Food Sharing Behavior in Male, but Not Female Marmosets in Family Groups

Abstract: Oxytocin (OT) is critical for lactation and maternal care, but OT and the related nonapeptide vasopressin are important for caregiving behaviors in fathers and alloparents as well. This experiment tested the effects of vasopressin and OT on food sharing in marmoset families. We treated caregivers (parents, siblings) with intranasal vasopressin, OT, or saline, and then paired them with the youngest marmoset in the family. Caregivers were given preferred food, and then observed for food sharing and aggressive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Leu 8 -OT treatment lead to greater transfer of food from fathers to offspring, by decreasing the rates of food sharing refusals (Saito & Nakamura 2011). In contrast, our lab showed that Pro 8 -OT treated male marmosets were less likely to engage in alloparental care via sharing food with their younger siblings (Taylor et al 2017). Importantly, many contextual and procedural features between these studies differed, making a direct comparison between the opposing Leu 8 - and Pro 8 -OT effects difficult.…”
Section: Parental Behaviormentioning
confidence: 79%
See 2 more Smart Citations
“…Leu 8 -OT treatment lead to greater transfer of food from fathers to offspring, by decreasing the rates of food sharing refusals (Saito & Nakamura 2011). In contrast, our lab showed that Pro 8 -OT treated male marmosets were less likely to engage in alloparental care via sharing food with their younger siblings (Taylor et al 2017). Importantly, many contextual and procedural features between these studies differed, making a direct comparison between the opposing Leu 8 - and Pro 8 -OT effects difficult.…”
Section: Parental Behaviormentioning
confidence: 79%
“…Second , when Pro 8 -OT treatments produce an effect on behavior it is almost always in the expected direction; Pro 8 -OT enhances mate-directed or mate-received behavior and reduces stranger-directed behavior. Two notable exceptions are the findings that young male marmosets treated with Pro 8 -OT reduce food sharing directed toward siblings (Taylor et al 2017), and adult marmosets treated with Pro 8 -OT increased time spent alone and reduced time spent with the mate (Cavanaugh et al 2014). Third , Leu 8 -OT treatments produced mixed effects on whether social behavior was enhanced or impaired, and Leu 8 -OT never enhanced a social behavior that Pro 8 -OT did not also enhance.…”
Section: Summary Of Pro8-ot and Leu8-ot Effects On Social Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of AVP to bind and activate primate OTRs was also tested, because AVP binds and activates OTRs, and AVP is known to affect social behavior in primates, including titi monkeys and marmosets (Caldwell et al, 2008;Jarcho et al, 2011;Taylor and French, 2015;Taylor et al, 2017). In all species except the titi monkey, AVP bound with much lower affinity to the OTR than Pro 8 -OT or Leu 8 -OT, and in all species AVP had lower potency for mobilizing Ca 21 than Pro 8 -OT or Leu8-OT.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these rodent data, it is useful to interpret studies involving OT and AVP in marmosets within the framework of aggression and anxiety, as well as within the framework of prosociality. Marmoset fathers refuse to share food to weaned and food‐independent juveniles more often when treated with AVP compared to saline, and among all marmoset caregivers, AVP increased aggressive vocalizations toward juveniles in a food‐sharing task (Taylor, Intorre, & French, ). This suggests that the increase in food refusals in AVP‐treated marmoset fathers may be mediated via food‐related aggression.…”
Section: Discussionmentioning
confidence: 99%